Inovasi Eksternal Leksikal Bahasa Sunda di Wilayah Perbatasan Cirebon: Kajian Dialektologi - Febianti, Dike; Wahya, Wahya; Lyra, Hera Meganova (Jurnal Bahasa dan Sastra, 2026)
This study examines lexical external innovation in Sundanese in Babakan District, Cirebon Regency, a linguistic border area between Sundanese and Cirebon Javanese. The research aims to (1) identify external lexical innovations, (2) analyze the factors driving them, and (3) examine their sociolinguistic impact on language use. A descriptive qualitative approach supported by quantitative distribution analysis was employed. Data were collected from 200 lexical items based on the GSKSKB (a combined Swadesh and cultural vocabulary list) through fieldwork with native speakers. Findings reveal that 61 lexical items (30.5%) represent external innovations, primarily from Indonesian (22%) and, to a lesser extent, from Cirebon Javanese (8.5%). These innovations occur across core lexical domains, including body parts, kinship, and basic vocabulary, indicating that even a stable lexicon is susceptible to change. Distribution patterns show varying stages of diffusion, from localized occurrences to widespread adoption. The analysis suggests that external innovation is shaped by linguistic accommodation and language prestige. Indonesian, as a high-prestige national language, is the primary source of lexical borrowing, while Cirebon Javanese reflects localized influence. These innovations coexist with native Sundanese forms, creating lexical competition rather than immediate replacement. This study contributes to Sundanese dialectology by providing empirical evidence of external innovation in a border region and highlights the interplay between language contact, diffusion, and sociolinguistic adaptation.